On International Integration of Emerging Sovereign Bond Markets - Agur, Itai (IMF Working Papers; Working Paper ;, 2018)
The paper investigates the international integration of EM sovereign dollar-denominated and local-currency bond markets. Factor analysis is used to examine movements in sovereign bond yields and common sources of yield variation. The results suggest that EM dollar-denominated sovereign debt markets are highly integrated; a single common factor that is highly correlated with US and EU interest rates explains, on average, about 80 percent of the total variability in yields. EM sovereign local currency bond markets are not as internationally integrated, and three common factors explain about 74 percent of the total variability. But a factor highly correlated with US and EU interest rates still explains 63 percent of the yield variation accounted for by common factors. That said, there is some diversity among EM countries in the importance of common factors in affecting sovereign debt yields.